Disentangling Structural Domains in Solution‐Processed 2D Lead Halide Perovskite by Transient Absorption Spectroscopy - Song, Mu‐Sen; Wang, Hai; Zhang, Yu‐Peng; Hu, Zi‐Fan; Zhang, Jia; Wang, Yuan; Zhao, Le‐Yi; Wang, Hai‐Yu (Laser & photonics reviews, 2025)
2D lead halide perovskites (LHPs) exhibit outstanding optoelectronic properties, making them utilized in various emerging applications. Understanding their fundamental properties is urgent for improving device performance. Here, the structural domains in 2D PEA2MAn‐1PbnI3n+1 films are studied by temperature‐dependent transient absorption (TA) measurements. For = 1 film at low temperatures, the ground state bleach (GSB) shows obvious splitting when the high‐energy state is resonantly excited, whereas only one GSB exists under low‐energy resonant excitation, indicating that the two split energy states correspond to different structural domains. For = 2 film, similar phenomena are observed, but the energy level difference between the two domains is decreased. With further increase of the inorganic layers number, the two domains can no longer be distinguished. In addition, by changing the organic cations, it is demonstrated that the two structural domains originate from distortions in the inorganic PbI6 octahedral frames. Finally, the possibility that the two energy states are from the formation of polaron states is ruled out by TA measurement on CsPbBr3 QDs. The results provide new insights into the structural domain properties of 2D LHPs, which directly influence the suitability of these materials for future optoelectronic devices. The study demonstrates that there are two structural domains exist in the = 1 and 2 films. As the number of inorganic layers number increases, the energy level difference between the two domains gets smaller. Thus, they predict the coexistence of the two domains in = 3 and 4 films.